Estudo da recuperação de óleo por drenagem gravitacional assistida por injeção de vapor - Barillas, Jennys Lourdes Meneses (2008)
Steam assisted gravity drainage process (SAGD) involves two parallel horizontal wells located in a same vertical plane, where the top well is used as steam injector and the bottom well as producer. The dominant force in this process is gravitational. This improved oil recovery method has been demonstrated to be economically viable in commercial projects of oil recovery for heavy and extra heavy oil, but it is not yet implemented in Brazil. The study of this technology in reservoirs with characteristics of regional basins is necessary in order to analyze if this process can be used, minimizing the steam rate demand and improving the process profitability. In this study, a homogeneous reservoir was modeled with characteristics of Brazilian Northeast reservoirs. Simulations were accomplished with STARS , a commercial software from Computer Modelling Group, which is used to simulate improved oil recovery process in oil reservoirs. In this work, a steam optimization was accomplished in reservoirs with different physical characteristics and in different cases, through a technical-economic analysis. It was also studied a semi-continuous steam injection or with injection stops. Results showed that it is possible to use a simplified equation of the net present value, which incorporates earnings and expenses on oil production and expenses in steam requirement, in order to optimize steam rate and obtaining a higher net present value in the process. It was observed that SAGD process can be or not profitable depending on reservoirs characteristics. It was also obtained that steam demand can still be reduced injecting in a non continuous form, alternating steam injection with stops at several time intervals. The optimization of these intervals allowed to minimize heat losses and to improve oil recovery